Percutaneous Nephrolithotomy and Horseshoe Kidneys - Basnet, Robin Bahadur; Shrestha, Anil; Shrestha, Parash Mani; Joshi, Biswa Raj (Nepalese Medical Journal, 2020)
Introduction: The most common fusion anomaly, horseshoe kidney, is associated with vascular anomalies, malrotation, anterior displacement of the collecting system, superior insertion of ureter into the pelvis, and a higher rate of ureteropelvic junction obstruction; thus increasing the chances of nephrolithiasis. We present our experience with percutaneous nephrolithotomy in this anomaly. Materials and Methods: A retrospective study of all the percutaneous nephrolithotomy performed by standard technique within four years at Bir Hospital was made. A comparison was made with similar cases with the anatomically normal location of the kidney. Intraoperative variables were recorded and postoperative stonefree status and complications were evaluated. Results: Six hundred and twenty-seven patients out of 691 who had undergone percutaneous nephrolithotomy in this period were included. Patients with nephrolithiasis in horseshoe kidney were younger, the incidence of multiple stones was more; without full staghorn calculus and occupying fewer calyces. Upper pole access was easier, a stone clearance of 85.42 % was achieved with no major complications in the horseshoe kidney. Conclusions: Percutaneous access and nephrolithotomy are safe in horseshoe kidney with a good stone clearance rate.